When is diminishment a form of enhancement? Rethinking the enhancement debate in biomedical ethics - Earp, Brian D.; Sandberg, Anders; Kahane, Guy; Savulescu, Julian (Frontiers in Systems Neuroscience, 2014)
The enhancement debate in neuroscience and biomedical ethics tends to focus on the augmentation of certain capacities or functions: memory, learning, attention, and the like. Typically, the point of contention is whether these augmentative enhancements are permissible for individuals with no particular ‘medical’ disadvantage along any of the dimensions of interest. Less frequently addressed in the literature, however, is the fact that sometimes the diminishment of a capacity or function, under the right set of circumstances, could plausibly contribute to an individual’s overall well-being: more is not always better, and sometimes less is more. Such cases may be especially likely, we suggest, when trade-offs in our modern environment have shifted since the environment of evolutionary adaptation. In this article, we introduce the notion of “diminishment as enhancement” and go on to defend a welfarist conception of enhancement. We show how this conception resolves a number of definitional ambiguities in the enhancement literature, and we suggest that it can provide a useful framework for thinking about the use of emerging neurotechnologies to promote human flourishing.